(Trade) War and Peace: How to Impose International Trade Sanctions - Gustavo de Souza; Naiyuan Hu; Haishi Li; Yuan Mei (Center for Economic Studies and ifo Institute (CESifo), 2023)
Trade sanctions are a common instrument of diplomatic retaliation. To guide current and future policy, we ask: What is the most cost-efficient way to impose trade sanctions against Russia? We build a quantitative model of international trade with input-output connections. Sanctioning countries choose import tariffs to simultaneously maximize their income and minimize Russia's income, with different weights placed on these objectives. We find, first, that for countries with low willingness to pay for sanctions against Russia, the most cost-efficient sanction is a uniform tariff on all Russian products of about 20%. Second, if countries that are willing to pay at least US0.70 for each US1 drop in Russian welfare, an embargo on Russia's mining and energy products – with tariffs above 50% on other products – is the most cost-efficient policy. Finally, if countries target politically relevant sectors, an embargo on Russia's mining and energy sector is the cost-efficient policy, even when there is low willingness to pay for sanctions.
Keywords: F13; O24; 330; trade sanctions; tariff; tariff competition